2009
DOI: 10.1007/s12257-008-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structures in conventional activated sludge system and membrane bioreactor (MBR)

Abstract: The microbial community structures of a conventional activated sludge and MBR systems treating the municipal wastewater were studied using Fluorescent áåJëáíì Hybridization (FISH) analysis to identify differences in both systems. The oligonucleotide probes specific for overall bacteria, including α-, β-, and γ-subclasses of mêçíÉçÄ~ÅíÉêá~, ammonia-oxidizing bacteria (káíêçëçãçå~ë), and nitrite-oxidizing bacteria (káíêçÄ~ÅíÉê) were used to compare the microbial community structure of both systems. A trend of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…For example, compared to conventional activated sludge, an MBR is typically operated at high MLSS concentrations, long sludge retention time, and high DO concentrations to control membrane fouling. Previous studies showed that different treatment processes could harbor distinct microbial community structures (37)(38)(39)(40). However, our study revealed that treatment process was not significantly correlated with most of the functional and phylogenetic groups except for the functional groups involved in C and N cycling and organic remediation.…”
Section: Discussioncontrasting
confidence: 71%
“…For example, compared to conventional activated sludge, an MBR is typically operated at high MLSS concentrations, long sludge retention time, and high DO concentrations to control membrane fouling. Previous studies showed that different treatment processes could harbor distinct microbial community structures (37)(38)(39)(40). However, our study revealed that treatment process was not significantly correlated with most of the functional and phylogenetic groups except for the functional groups involved in C and N cycling and organic remediation.…”
Section: Discussioncontrasting
confidence: 71%
“…Nitrogen and phosphorous recovery rate have improved on the introduction of biofilm to the conventional activated sludge membrane. Proteobacteria, Nitrosomonas,and Nitrobacter are commonly used microbes in MBR (Baek and Pagilla 2009).…”
Section: Membrane Biofilm Reactor (Mbr)mentioning
confidence: 99%
“…Indeed, in MBR system, the selection of bacteria is strictly based on metabolic or kinetic factors rather than the ability of bacteria to aggregate in dense and settling flocs. From this point of view, MBR are characterized by a greater variety of the microbial community compared to a CAS system [17], thus resulting in a better enrichment of the accumulating biomass. Based on the above considerations, the selective enrichment of MMC in MBR system remain a promising solution to improve the overall production of biopolymers, although the operating conditions should be optimized to maximize the production yield.…”
Section: Production Of Biopolymers Using Fermented Real Citrus Wastewater: Effect Of C/nmentioning
confidence: 99%